2021
DOI: 10.1007/s40121-021-00455-1
|View full text |Cite|
|
Sign up to set email alerts
|

Real-World Outcomes in Historically Underserved Patients with Chronic Hepatitis C Infection Treated with Glecaprevir/Pibrentasvir

Abstract: Introduction: Glecaprevir/pibrentasvir is approved for treating chronic hepatitis C virus (HCV) genotypes (GT) 1-6. We evaluated realworld effectiveness, safety, and patient-reported outcomes of glecaprevir/pibrentasvir in underserved patient populations, focusing on persons who use drugs infected with HCV.Methods: Data were pooled from nine countries (13 November 2017-31 January 2020). Patients had HCV GT1-6, with or without compensated cirrhosis, with or without prior HCV treatment and received glecaprevir/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
3
10
1
Order By: Relevance
“…The favorable safety profile of G/P in this real-world cohort was consistent with that reported in previous clinical trials and real-world studies of G/P for patients with CC [ 8 , 12 ], including EXPEDITION-8, where no serious drug-related AEs or discontinuations due to AEs were reported [ 9 ]. Furthermore, the high SVR12 rates observed in patients traditionally considered as being underserved are in line with the findings from studies which have demonstrated that G/P treatment was highly effective in patients with substance abuse and psychiatric comorbidities [ 13 , 14 , 17 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The favorable safety profile of G/P in this real-world cohort was consistent with that reported in previous clinical trials and real-world studies of G/P for patients with CC [ 8 , 12 ], including EXPEDITION-8, where no serious drug-related AEs or discontinuations due to AEs were reported [ 9 ]. Furthermore, the high SVR12 rates observed in patients traditionally considered as being underserved are in line with the findings from studies which have demonstrated that G/P treatment was highly effective in patients with substance abuse and psychiatric comorbidities [ 13 , 14 , 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…A few real-world studies have evaluated G/P in patients with CC, with a special interest in harder-to-treat groups such as those with comorbidities, those with HCV GT3 infection, people who use drugs (PWUD), those with a psychiatric disorder, and those with other barriers to treatment [ 11 14 ]. These studies have shown that SVR12 rates with G/P remain high and ≥ 98% in the PP population of GT1–6 patients [ 11 , 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients with current or former drug abuse was lower than expected (12%) compared with epidemiological data from Italy which estimated that 49% of patients with HCV are people who inject/injected drugs [ 4 ]. The proportion of patients with alcohol dependence was also lower (4.8%) than previously reported [ 23 , 34 ].…”
Section: Discussioncontrasting
confidence: 68%
“…6 The overall SVR12 rate of non-GT3-infection versus GT3-infection in ITT population Fig. 7 The overall SVR12 rate of non-cirrhosis versus cirrhosis in ITT population patients participating in clinical trials, these patients are more heterogeneous and more inclusive of marginalized populations [38]. They provide valuable information for patients, doctors, decision-makers, and payers and are an important supplement to the results of clinical trials [19].…”
Section: Discussionmentioning
confidence: 99%